2022
DOI: 10.3389/fvets.2021.829872
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis and Bone Metabolism in Goats Fed a Low Protein Diet

Abstract: The objective of this study was to investigate the effects of low-protein diets on blood calcium (Ca) level, bone metabolism, and the correlation between bone metabolism and blood calcium in goats. Twenty-four female Xiangdong black goats with similar body weight (19.55 ± 3.55 kg) and age (8.0 ± 0.3 months) were selected and allocated into two groups: control group (CON, 10.77% protein content) and low-protein group (LP, 5.52% protein content). Blood samples were collected on days 1, 4, 7, 16 and 36 before mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The serum concentrations of CT, OC, and HYP decreased with dietary Ca levels ranging from 0.50% to 0.68% and then ascended with dietary Ca levels up to 0.98%. The OC, HYP, and ALP concentrations can reflect the Ca metabolism of animals [ 32 , 33 ]. Previously, a study showed that the serum OC and ALP contents of growing sheep and goats increased with the increase in dietary Ca concentrations [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serum concentrations of CT, OC, and HYP decreased with dietary Ca levels ranging from 0.50% to 0.68% and then ascended with dietary Ca levels up to 0.98%. The OC, HYP, and ALP concentrations can reflect the Ca metabolism of animals [ 32 , 33 ]. Previously, a study showed that the serum OC and ALP contents of growing sheep and goats increased with the increase in dietary Ca concentrations [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMSC grown in a decreased AA concentration showed early senescence and cell death [ 173 ]. Whilst AA availability in low-protein intake (LPD) has been shown to impair bone mass during growth through IGF-I with age [ 174 ], there is little known about how LPD effects the overall bone health and BMSC fate differentiation in young adults [ 175 ]. Other studies of mouse maternal protein intakes have also shown to affect foetal bone formation and mineral quality; yet, these findings were gender-specific and inconsistent among all experimental groups [ 176 ].…”
Section: The Role Of Environmental Factors In Msc Aging and Diseasementioning
confidence: 99%